People's Republic of China poverty reduction and regional cooperation fund annual report 2020 - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This report provides information about the technical assistance and grants provided through the People’s Republic of China Poverty Reduction and Regional Cooperation Fund (PRC Fund) in 2020.
Executive Summary - - PRC Fund at a Glance - - Background - - Overview of Fund Operations, 2020 - - Overview of Fund Operations, 2005–2020 - - Partnering: The Way Forward - - Appendixes.
Keywords: Cofinancing -- China; International finance -- Economic aspects -- China; Cofinancing -- International cooperation -- China